Clinical Interpretation of Cardiopulmonary Exercise Testing: Current Pitfalls and Limitations - Neder, J. Alberto; Phillips, Devin B.; Marillier, Mathieu; Bernard, Anne-Catherine; Berton, Danilo C.; O’Donnell, Denis E. (Frontiers in Physiology, 2021)
Cardiopulmonary exercise testing (CPET) remains largely underused in clinical practice. Apart from operational aspects (e.g., high equipment costs, limited availability, poor reimbursement relative to time spent on testing performance and interpretation), there are several shortcomings on its interpretation which have shed a negative light on CPET as applied to pulmonology. We herein provide a concise perspective on some key contemporary issues, including: a) over-reliance on rigid interpretative algorithms, b) incorrect display of graphical data, c) underestimation of dyspnea assessment, d) misinterpretation of a “preserved” peak O2 uptake as evidence of normality, e) lack of appreciation of the confounding effects of obesity, f) failure to recognize the poor diagnostic performance of CPET in indicating cardiac disease, g) misdiagnosis of mechanical-ventilatory limitation, h) overlook of the limitations of non-invasive assessment of pulmonary gas exchange, and i) over- and under-call of a chaotic breathing pattern and dysfunctional breathing in dyspneic subjects.